Participation without democracy : containing conflict in Southeast Asia - Rodan, Garry, 1955- (Cornell University Press, 2018)
"With an empirical focus on regimes in Singapore, the Philippines, and Malaysia, the author examines the social forces that underpin the emergence of institutional experiments in democratic participation and representation"--